Rancang Bangun Multilevel Inverter dengan Filter Pasif L-C-L dan Teknologi IoT Untuk Memantau Perubahan Kecepatan Motor Induksi Satu Fasa - Gesang Amar; Noer Soedjarwanto (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2024)
Multilevel inverter is a type of inverter used to generate AC signals with adjustable frequency and better quality. L-C-L passive filter is used to eliminate harmonic distortion in the generated AC signals. Meanwhile, IoT technology is used to remotely monitor and control the speed of the motor through a mobile application. In this thesis, the design of a flying capacitor multilevel inverter is used as an induction motor speed controller with the resulting Total Harmonic Distortion (THD) can be reduced if you add a level to the inverter. Then, L-C-L passive filter is designed to eliminate harmonic distortion in the generated AC signals. Furthermore, the implementation of IoT technology is carried out using Blynk IoT platform. The test results show that the multilevel inverter with L-C-L passive filter successfully generates AC signals with better quality compare without L-C-L passife filter. In addition, IoT technology is successfully implemented and allows users to remotely monitor and control the speed of the motor through a mobile application. Thus, the use of multilevel inverter with L-C-L passive filter and IoT technology can effectively increase the efficiency and control of single-phase induction motor. Keywords: multilevel inverter, L-C-L passive filter, IoT, induction motor, total harmonic distortion.